La présence communiste au Québec (1929-1939) ou la présence de « l'homme au couteau entre les dents » - Dansereau, Bernard (Bulletin d'histoire politique, 2001)
Examines the presence and struggles of the Communist Party of Canada (le Parti communiste canadien (PCC)) in Quebec during the 1930s. It highlights the challenges faced by the PCC, including widespread anticommunism from the government, the Catholic Church, and conservative labour unions. The PCC sought to organize workers through independent unions like the Workers Unity League and engaged in social struggles, including unemployment protests and antifascist campaigns. Despite some successes in labour movements and antifascist efforts, the PCC failed to become a mass party, remaining largely isolated and marginalized, especially among francophone workers. The article also discusses the PCC's strategic shifts, from ultra-revolutionary rhetoric to a united antifascist front, and its eventual decline during World War II. Overall, the PCC's efforts were significant in challenging capitalism and advocating for workers' rights, but its influence remained limited in Quebec's political and social landscape.